Heterogeneous spatiotemporal streamflow response to large-scale climate indexes in the Eastern Alps - Teresa Perez Ciria; David Labat; Gabriele Chiogna (Zenodo, 2022)
Analyzing temporal and spatial variability of river discharge and the impacts of large-scale climate oscillations on hydrological systems are of particular interest in Alpine catchments, which have been proved to be especially sensitive to climatic drivers. The impact of climate oscillationindexes may show a delayed response and therefore the correlation between climatic drivers and streamflow is challenging to be properly identified. For this purpose, wavelet transform (WT) is recognized as a suitable tool able to determine the crucial scales of variability. In this work, first we explore the periodicities and the coherence among several climatic indexes: North Atlantic Oscillation Index (NAO), Mediterranean Oscillation Index (MO), Greenland Blocking Index (GB), and Artic Oscillation Index (AO). This analysis shows the complementary information that different oscillation indexes provide and the need to consider their impacts on streamflow simultaneously. Previous work revealed a heterogeneous and complex response of the Inn river basin at long temporal scales, which could not be linked to analyzed anthropogenic impacts such as dams’ construction and hydropower plants operation. Therefore, the trigger of changes in streamflow variability remained unclear. In this study, we elaborate a classification based on all considered indexes’ coherence with fifty gauging stations of the Inn river catchment. We quantify similarity among stations with a focus on yearly and longer temporal scales. The results highlight the heterogeneous response of the streamflow towards changes in climatic indexes and give an overview of the possible drivers of detected long-term alterations. NAOand GB extreme phases are connected with cold winters and hot summers. We observe that from the 1980s changes detected in the streamflow behavior at yearly and longer temporal scales are in line with emerging patterns of the climatic indexes, such as the shift from constant to intermittent periodicities of the MO index. AO coherence displays a higher ...